Social Media Activities by Women with Iddah Period Based on Islamic Law Perspectives: Study in Sei Lepan Subdistrict community, Langkat Regency - Abidin , Muhammad; Sukati , Sukati; Siregar , Ramadhan Syahmedi (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This research aims to (1) determine the social media content of women with Iddah period while using social media in Sei Lepan Subdistrict; (2) to determine the understanding of women with Iddah period regarding the limits of using social media during Iddah in Sei Lepan Subdistrict; and (3) to figure out the study Islamic Law concerning limits on the permissibility of using Social Media for Women with Iddah period. To achieve these aims, the researchers designed this study using qualitative methods to provide a detailed explanation of how women with Iddah period perform. This research used normative empirical research that took references from books, articles, and journals whose subjects were compared to phenomena in the field. The results of this research are: There are several types of social media content for women with Iddah period by social media in Sei Lepan District. The understanding of women with Iddah period and use social media in Sei Lepan Subdistrict is still relatively low. The awareness of women with Iddah period by social media is still relatively low. Islamic law divides the study on the permissibility of women who adhere to the law using social media into two categories: makruh and haram.